Case studies in public budgeting and financial management - Khan, Aman (Kendall/Hult Publishing company, 1994)
A resource for administrators seeking innovative ideas and supporting precedents in formulating policy, this book also provides a useful textbook for public administration and policy students. It employs a wealth of case studies in budgeting and financial management to demonstrate strategies in system implementation, policy formulation, government